Bangladesh strategies for development - Grieve, Roy H.; Huq, M. M.; Bangladesh Economic Association; BEA UK Forum (Dhaka, Bangladesh : University Press Ltd., 1995)
Proceedings of the inaugural conference of the BEA UK Forum, held at the University of Strathclyde on 7 May 1994.
"Published in collaboration with Bangladesh Economic Association (BEA) and the BEA UK Forum"--T.p. verso.
Includes bibliographical references and index.
Keywords: Economic policy -- Bangladesh; Bangladesh -- Economic policy -- Congresses; Bangladesh -- Economic conditions -- Congresses; Bangladesh -- Commercial policy -- Congresses